Work Conflict, Workload, and Employee Performance in Retail: A Quantitative Study: Dampak Konflik Kerja, Beban Kerja, dan Stres Kerja terhadap Kinerja Karyawan: Studi Kuantitatif di Industri Ritel - Vicki Dias Tatiningrum Kuncoro; Hasan Ubaidillah (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to investigate the influence of work conflict, workload, and work stress on employee performance in a small and medium-sized retail business. The research employed a quantitative approach, utilizing hypothesis testing and involving a sample of 40 employees from UMKM Moana Daily Style. The analysis utilized correlation coefficient (R), classical assumption tests, and multiple linear regression in IBM SPSS Statistics version 26. The data were collected through a questionnaire using a Likert scale, with reliability and validity tests conducted. The findings revealed significant relationships between work conflict and employee performance, workload and employee performance, as well as work stress and employee performance. These results highlight the importance of managing work conflict, workload, and work stress to enhance employee performance in the retail industry. The implications of the study suggest the need for organizations to implement strategies that promote conflict resolution, workload management, and stress reduction to optimize employee performance. Highlights: The study examines the impact of work conflict, workload, and work stress on employee performance in the retail industry. Findings indicate significant relationships between work conflict, workload, work stress, and employee performance. The research emphasizes the importance of managing work conflict, workload, and work stress to enhance employee performance in retail organizations. Keywords: Work Conflict, Workload, Work Stress, Employee Performance, Quantitative Study.